Organisation spatiale de la fracturation de détente mécanique de versant en carrières souterraines. Application aux plateaux des calcaires éocènes du Bassin de Paris - Alain Devos; Laurent Chalumeau; Nicolas Bollot; Christelle Sosson; Éléonore Barre; Olivier Lejeune; Geoffroy Gobancé (Physio-Géo)
Fracturing network is studied in underground quarries where slope mechanical distension is characterized. Thirty quarries are chosen in plateaus of Lutetian limestone of Paris basin (north-east France). The working method consists in realizing topography of underground quarries and in measuring fracturing network (orientation, width and filling) by fracturing index and statistic analyses. The fracturing network depends to geomorphological context and to length to the slope. Indeed, sites of spur and dale of order 1 are characterized by an orthogonal fracturing debiting of small block sizes. The other sites (front slope, slope of rectilinear valley, crest) have a parallel fracturing network to the slope without partitioning. Fracture density increases from the center of the plateau to the slope indicating a mechanical distension that comes with cambering, lateral spreading and sliding block. The fracturing network is the seat of karst in Lutetian limestone (palaeokarst).